Preoperative position splint versus skin traction in patients with hip fracture: An experimental study. (February 2018) - Tosun, Betul; Aslan, Ozlem; Tunay, Servet
Abstract: Aim: The aim of the study was to compare the effects of a preoperative position splint and skin traction on pain, comfort, complications, and satisfaction with the treatment and care for patients with hip fracture. Method: This randomized trial was conducted with a total of 68 patients with hip fracture in a tertiary care hospital in Turkey. Preoperatively, a position splint was applied to the patients in the intervention group (n = 34) and skin traction was applied to patients (n = 34) in the control group. Outcomes studied were pain, comfort, satisfaction and complications. Results: Mann-Whitney U Test showed a significant difference between the position splint group and skin traction group regarding pain severity after the application (p < .05). A significant difference was demonstrated between the two groups concerning comfort levels after the application (p < .05). The position splint group was significantly more satisfied with the treatment and care than the control group in the later period after the application (p < .05). The number of preoperative complications in the position splint group was significantly fewer than that of the skin traction group in the preoperative period (p < .05). Conclusion: Preoperative position splint application in patients with hip fracture relieved pain and complications and increased comfort and satisfaction with treatment and care.